PUTIN AFTER PUTIN - Paraschiva Bădescu (Romanian Journal of Historical Studies, 2021)
The coming year for Russia will be defined by the new parliament, new government and the presidential elections in March 2012. Vladimir Putin certainly will win and return to the Kremlin next year. Under Putin's first two presidential mandates (2000-2008) Russia has returned to the international arena as an important player. Now, Russia is different, international situation is also different and very challenging. Putin's return might be followed by the Russia's stronger affirmation as an important international player. This study analyzed the first two presidential mandates, context, perspectives of the future internal and external evolution and significance of Putin's return, impact and challenges he might face.